Analysis of the Ability of Various Types of Microalgae to Inhibit the Growth of Fluorescent Vibrio Bacteria - Ahmadirrahman Fajrihanif; Nursyahran Nursyahran; Ince Ayu Khairana Kadriah; Endang Susianingsih; Nurhidayah Nurhidayah; Nurbaya Nurbaya (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Environmentally friendly disease prevention alternatives in tiger shrimp cultivation have begun to be widely implemented, one of which is the use of microalgae, which play an important role in aquaculture activities. In addition to functioning as natural food, microalgae also have the ability to control microbiological communities in aquatic environments through various mechanisms, both by inhibiting and supporting the growth of other microorganisms. This study aims to determine the ability of the microalgae Porphyridium sp, Vulgaris sp, Phaeodactylum sp, and Nannochloropsis sp in inhibiting the growth of fluorescent Vibrio bacteria, known as one of the causes of vibriosis in shrimp cultivation. The results showed that all microalgae tested had antibacterial properties, especially the type of Nannochloropsis sp, which was able to significantly reduce the number of bacteria over a longer observation period, so it has great potential to be used as an environmentally friendly natural ingredient for the prevention of diseases caused by bacteria in shrimp cultivation.